STUDY OF DYNAMIC FRACTURE OF X80 NATURAL GAS PIPELINE - LV JinJie; ZHAO JunHua; YU PeiShi (Jixie qiangdu)
A finite element model of the dynamic fracture in a full size gas pipeline is established based on the cohesive zone model. The dynamic crack growth of X80 pipeline steel was simulated using this model and the quantitative relationship between the crack growth rate and the internal pressure predicted is in agreement with the existing semi-empirical formula. Based on this model, some key parameters which are difficult to be directly measured in pipe blasting test（such as the crack tip opening angle, the stress and strain field surrounding the crack tip, energy dissipation, etc） could be quantitatively studied especially when the crack speed is very high. Accordingly, the proposed model would be a supplementary mean for the full-scale test. Moreover, the crack arrest design of the full-scale pipeline is also discussed based on this model.